Investigation of the reaction D(4He, γ)6Li at ultralow energies; Physics of Particles and Nuclei Letters; Vol. 13, iss. 2 - Burkatovskaya Yu. B. Yuliya Borisovna; Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Krylov A. R. Aleksandr Romanovich; Lysakov A. S. Anton Svyatoslavovich; Gazi S. Stefan; Guran Y. Yezhek; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Sadovsky A. B. Andrey Borisovich; Tuleushev Yu. Zh. Yury Zhianshakhovich; Filipovich M. Marius; et al. (Physics Of Elementary Particles And Atomic Nuclei. Experiment, 2016)
Title screen